Sabit Kick Speed Profile and General Speed of Pencak Silat Club Achievement - M. Riski Adi Wijaya; Deny Pradana Saputro; Alfira Nuril Aissya (STKIP Muhammadiyah Kuningan, 2022)
This research aims to describe the general speed profile and the specific speed of the athletes of the achievement Pencak silat club (PSP). The method used in this study is a non-experimental quantitative method with a quantitative descriptive approach. The sample of this study amounted to 20 athletes of Pencak silat achievement Pencak silat club (PSP). The data collection technique in this study uses a Pencak silat parameter test (Lubis, J & Wardoyo, 2016), a general speed test using a running speed test as far as 20 meters, while a particular speed test using a sabit kick speed test for 10 seconds. The data processing technique uses a percentage for each classification with a formula (Anas Sudijono, n.d.). This study found results with a rate of 5% of achievement Pencak silat club athletes have the excellent classification, and 95% have a little variety in available speed through a 20-meter running speed test. In comparison, a remarkable speed 10% have the perfect classification, and 90% have good classification through tests Sabit kick speed for 10 seconds. The researcher concludes that the physical component of velocity is a crucial component to be improved in supporting achievement, both speed in general and speed specifically according to the needs of the sport of Pencak silat.